2014
DOI: 10.1186/2040-7378-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric characterization of brain dendritic cell subsets after murine stroke

Abstract: BackgroundSterile inflammation is a substantial element of post-stroke pathophysiology with the determination of autoimmunity versus tolerance being one of its most important aspects. It is believed that this determination is initiated relatively early after stroke onset by clearing macrophages and migratory dendritic cells (DC). However, the phenotypic differentiation of macrophages and DC is intricate particularly in the disease context. Here, we utilized a set of surface markers used in mucosal immunity res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…+ cells has been reported [9]. Whether these cells will reach the draining lymph nodes to present antigen to T cells remains elusive, but our study of tonsils from patients with stroke, i.e., lymphoid tissue located within the draining pathways of the CNS, showed neural antigens on migratory BDCA1…”
Section: Innate Versus Adaptive Immunity In Strokementioning
confidence: 76%
See 1 more Smart Citation
“…+ cells has been reported [9]. Whether these cells will reach the draining lymph nodes to present antigen to T cells remains elusive, but our study of tonsils from patients with stroke, i.e., lymphoid tissue located within the draining pathways of the CNS, showed neural antigens on migratory BDCA1…”
Section: Innate Versus Adaptive Immunity In Strokementioning
confidence: 76%
“…Acute brain damage generates a genuine inflammatory reaction triggered by necrotic neuronal cells that leak their content to the extracellular space and trigger strong innate immune responses involving resident microglia and infiltrating leukocytes [4,5]. Notably, antigen-presenting cells (APC) accumulate in the brain parenchyma during the days that follow experimental stroke [6][7][8][9][10]. These cells express major histocompatibility complex (MHC) class II and co-stimulatory molecules, as well as markers of conventional dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes/macrophages Decreasing the number of monocytes; polarization of M2 phenotype; increasing production of IL-10; reducing phagocytic capability [43], [44], [45] Neutrophils Impairment in ROS production; reduction of phagocytosis; shortening life-span as a result of spontaneous apoptosis [43,[46][47][48][49] Dendritic cells Decreasing number of circulating DCs; anergic response to TLR3 and TLR4 stimulations; incapable of priming effective cellular immune response; disturbed infiltration and aberrant phenotypic differentiation [50][51][52][53] T lymphocytes Reducing proportion of peripheral T cells; disturbing response to antigens; polarization of anti-inflammatory phenotypes; inducing imbalance between Tregs and proinflammatory phenotypes of T cells [54][55][56][57][58] sepsis, but they are rarely found in the normal brain [66]. Neutrophils accumulating in the central nervous system jeopardize brain cells by releasing inflammatory cytokines, increasing the activity of myeloperoxidase, and promoting oxidative damage [74].…”
Section: Types Of Immune Cells Changes In Function and Activity Refermentioning
confidence: 99%
“…Yilmaz and colleagues found that circulating DC precursors underwent transient decrease after acute stroke, which was correlated with the severity of brain injury [51]. Furthermore, disturbed infiltration and aberrant phenotypic differentiation of DCs were also characterized under brain dysfunction [52,53]. However, the precise mechanisms of the dysfunction of DCs and its significance in host immunosuppression remain to be clarified.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…First, we did not assess the time course, detailed location, or number of DC in the mouse brains before or after stroke induction. Several groups have previously done this and described a uniform dynamic of DC infiltration in rodents subjected to focal cerebral ischemia: cDC (defined by CD11b + /CD103 + ) were virtually absent in naive murine brain tissue [31] . In the ischemic core of rat brains, the presence of DC expressing major histocompatibility complex II has been reported as early as a few hours after stroke onset, with a maximum on day 6, but not in animals without stroke [32] .…”
Section: Discussionmentioning
confidence: 99%